Usage of WhatsApp in relation to employee engagement in a telecommunication company - Ariffin, Zaifunizam; Omar, Siti Zobidah (Human Resource Management Academic Research Society, 2018)
WhatsApps application, the most talk-about mobile MIM application made available for any smartphone in the market. WhatsApp allows exchanging of real time text messages either to individual or group. The usage of WhatsApp has changed the way people communicate either personally and professionally. This paper is to investigate the relationship of WhatsApp usage and employee engagement in the organization. Almost all respondents use Whatapps and believe WhatsApp is a useful communication application. The paper indicates that there is a relationship between WhatsApp usage and employee engagement. Thus, WhatsApps application may be used as an effective internal communication tool to disseminate and sharing information.